Lexical innovations in the domain of geometry in Martianus Capella’s De Nuptiis Philologiae et Mercurii (Minerva, 2019)
Ancient Latin geometry has been transmitted by a not very large number of texts. Martianus Capella’s text excels over these. The most outstanding contribution of his work to the development of expression of this subject in Latin was likely the coining of terms by usual procedures in a Greek-originated discipline: loan and calque, grounded on an ancient Latin layer. In this paper we intend to study the most important words managing a method of analysis of the technical lexicon, paying attention to the usage patterns and contexts of use.
Keywords: Neologisms; geometry; Martianus Capella; mathematic and scientific lexicon